2009
DOI: 10.1002/ss.315
|View full text |Cite
|
Sign up to set email alerts
|

A statewide approach to creating veteran‐friendly campuses

Abstract: This chapter discusses a statewide response to the needs of veterans, military members, and their families. Specifically, it addresses the collaboration between Minnesota Department of Veterans Affairs‐Higher Education Veterans Programs, St. Cloud State University, and a student veteran organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Cloud State University (SCSU), the Minnesota Department of Veterans Affairs, and the SCSU Student Veterans Organization collaborated after repeatedly hearing that it was important for the veterans to feel a sense of belonging and be part of the campus community. One of the recommendations in their article to facilitate these needs was to provide an area that allows for networking with other veterans (Lokken, Pfeffer, McAuley & Strong, 2009). Coulter, Goin and Gerard (2004) found that graduate students also have specific needs for a designated meeting area to focus on professional development workshops and a venue for social interaction with peers.…”
Section: Discussionmentioning
confidence: 99%
“…Cloud State University (SCSU), the Minnesota Department of Veterans Affairs, and the SCSU Student Veterans Organization collaborated after repeatedly hearing that it was important for the veterans to feel a sense of belonging and be part of the campus community. One of the recommendations in their article to facilitate these needs was to provide an area that allows for networking with other veterans (Lokken, Pfeffer, McAuley & Strong, 2009). Coulter, Goin and Gerard (2004) found that graduate students also have specific needs for a designated meeting area to focus on professional development workshops and a venue for social interaction with peers.…”
Section: Discussionmentioning
confidence: 99%
“…Lokken and colleagues have described a military-friendly campus as an institution that strives to identify and remove barriers to the educational goals of veterans and to create smooth transitions between military life and college life [9]. Such campuses also enhance campus awareness of the student veteran population and develop proactive support programs to meet student veterans' needs [10].…”
Section: Emergent Themesmentioning
confidence: 96%
“…In general, however, higher educational institutions need to go beyond simply creating veteran centers to assess and address other educational barriers to create a truly comprehensive "veteran friendly" environment (Francis & Kraus, 2012;Kupo, 2010;Lokken, Pfeffer, McCauley, & Strong, 2009). For example, colleges and universities that streamline the admissions process for the student veteran facilitate the re-integration of these individuals, in accordance with their transitional situation.…”
Section: Role Of Higher Education In Veteran Support and Retentionmentioning
confidence: 99%
“…This can lead, often unintentionally, to the existence of a non-supportive environment for this population that will ultimately force the student veteran to withdraw and/or enroll in another institution perceived to be better able to support their education and transition. Lokken et al (2009) noted that higher educational institutions making every effort to promote a positive environment revealing a commitment to supporting the veteran student in the transition from military to civilian college life will be considered "veteran friendly" and will increase the number of student veterans' enrolled at their institution. Another issue that arises in this context is the need for more expensive colleges and universities with high tuition rates to reduce costs for student veterans and accept the maximum Post-9/11 educational benefits allotments.…”
Section: Certifying Official Rolementioning
confidence: 99%